2020
DOI: 10.3389/fbioe.2020.00838
|View full text |Cite
|
Sign up to set email alerts
|

A Sensor Fusion Approach to the Estimation of Instantaneous Velocity Using Single Wearable Sensor During Sprint

Abstract: Power-Force-Velocity profile obtained during a sprint test is crucial for designing personalized training and evaluating injury risks. Estimation of instantaneous velocity is requisite for developing these profiles and the predominant method for this estimation assumes it to have a first order exponential behavior. While this method remains appropriate for maximal sprints, the sprint velocity profile may not always show a first-order exponential behavior. Alternately, velocity profile has been estimated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…The Fieldwiz and Physilog 5 wearable sensors were chosen because they have already been used successfully for continuous analysis of running in the field (Apte et al, 2020;Meyer et al, 2021). Fieldwiz was used with a sampling frequency of 200 Hz for the IMU, 250 Hz for the ECG, and 10 Hz for the GNSS receiver.…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…The Fieldwiz and Physilog 5 wearable sensors were chosen because they have already been used successfully for continuous analysis of running in the field (Apte et al, 2020;Meyer et al, 2021). Fieldwiz was used with a sampling frequency of 200 Hz for the IMU, 250 Hz for the ECG, and 10 Hz for the GNSS receiver.…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…However, foot-based IMUs and pressure insoles provide higher accuracy for the estimation of contact time and GRF (Falbriard et al, 2018). It is possible to estimate stride length as a combination of the running speed measured from a shank or an upper back sensor (Yang et al, 2011;Apte et al, 2020), and the cadence from a sacrum or foot sensor (Lee et al, 2010;Falbriard et al, 2018). While previous research has shown the measurement of sagittal hip angles to be possible for fast movements (Fasel et al, 2018), the accuracy of this measurement is susceptible to soft tissue artefacts.…”
Section: Recommendations For Using An Imu-based Wearable Sensor Setupmentioning
confidence: 99%
“…IMU solutions use fusion sensing to estimate velocity [ 37 ]. Thus, despite their practical benefits, some issues related to accuracy and precision should be considered.…”
Section: Introductionmentioning
confidence: 99%